Is Overimitation a Uniquely Human Phenomenon? Insights From Human Children as Compared to Bonobos. Issue 5 (24th July 2017) - Clay, Zanna; Tennie, Claudio
Abstract : Imitation is a key mechanism of human culture and underlies many of the intricacies of human social life, including rituals and social norms. Compared to other animals, humans appear to be special in their readiness to copy novel actions as well as those that are visibly causally irrelevant. This study directly compared the imitative behavior of human children to that of bonobos, our understudied great ape relatives. During an action‐copying task involving visibly causally irrelevant actions, only 3‐ to 5‐year‐old children ( N = 77) readily copied, whereas no bonobo from a large sample did ( N = 46). These results highlight the distinctive nature of the human cultural capacity and contribute important insights into the development and evolution of human cultural behaviors.